MOCK conference as a tool for interpreters’ skills development: A case study - Mirzoyeva, Leila; Nurmetov, Diyar; Siswantoyo, Siswantoyo (LPMPP Universitas Negeri Yogyakarta, 2025)
Mastering skills in consecutive interpretation is indispensable for translator profession. The MOCK Conference, as a teaching tool, should be utilized to model the real-life conditions faced by interpreters in their work. This case study aims to identify the benefits of the MOCK Conference and the challenges encountered by trainee translators. The study involved 45 senior students from a private university in Kazakhstan. Data were collected through a survey, which included a Likert-scale questionnaire and open-ended questions for trainee translators. These were then analyzed using descriptive percentages. The results indicated that the respondents positively viewed the opportunities to develop key professional skills and competencies such as bilingual and cross-cultural competence, subject-specific knowledge, and the application of language-specific strategies. These competencies were considered by the participants to be the most essential interpreters’ skills for successful performance in their prospective careers. Additionally, the study revealed that some challenges arose during the MOCK Conference process. Stress, concentration difficulties, note-taking challenges, and time management issues were identified by the research participants as the main obstacles faced during the procedure. The core findings of the study have several implications for pre-service interpreters training, including the evaluation of positive and negative aspects of the MOCK Conference as interpreters training tool, and suggestions for future research.